Effectiveness of Combination Flexi-Bar Shoulder Exercise to the Kinesiotaping Application on Increasing Upper Extremity Proprioceptive Ability and Shooting Accuracy in Archery Athletes at Gandawa Archery Club - Dinihari, Embun; Indira Vidiari Juhanna; Syahmirza Indra Lesmana (PT Inovasi Pratama Internasional, 2025)
Kinesiotaping is passive stabilisator, so it is necessary to have a combination of one intervention such as adding Flexi-bar Shoulder Exercise (FSE) as an active proprioceptor stimulator to optimize joint stability and optimalize shooting accuracy for archery. The research method used was a quasi experiment pre and post-test group control with 22 archery athlete, divided into a control group that only received kinesiotaping, and a intervention group that received kinesiotaping and FSE 3 times a week for 4 weeks. Subjects were assessed for proprioceptive ability using the joint position sense test (JPS) of abduction and flexion and shooting accuracy. Based on the difference test pre and post the control group, there were significant differences in flexion JPS (p=0.00), abduction JPS (p=0.00), and shooting accuracy (p=0.03), for the treatment group, there were significant differences in flexion JPS (p=0.00), abduction JPS (p=0.00), and shooting accuracy (p=0.03). Based on the comparison test between the control and treatment groups, there were no significant differences proprioceptive abilities in flexion (p=0.151) and abduction (p=0.00) as well as in shooting accuracy (p=0.163). Combination of FSE with kinesiotaping, can improve proprioceptive abilities and shooting accuracy but did not provide a different effect than the Kinesiotaping group